Evolving definitions of frailty. (October 2007) - de Saint-Hubert, Marie; Swine, Christian
This article presents the current status of the definitions of frailty. The theoretical definitions are summarized, and the main elements of these definitions are developed. Frailty as a geriatric syndrome is briefly put into debate, and a model showing the relationships between the factors involved and the outcomes of frailty is proposed. The dynamics of functional decline and geriatric syndromes are put into the perspective of different stages of frailty. For the practical use of the concept, the operational definitions and the principal tools, indices and scales from the literature are briefly described, along with their main characteristics.